2012
DOI: 10.2298/gensr1203561k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound influence on coleoptile length at Poaceae seedlings as valuable criteria in prebreeding and breeding processes

Abstract: The study includes research on the effect of ultrasound on the ability of seed germination and coleoptile development of cereal landraces (fam. Poaceae): oat (Avena sativa L.) brodski, rye (Secale cereale L.) rakotinska, Triticale svetinikolsko and soft wheat (Triticum aestivum L.) govrlevska. The experiment with ultrasound was carried out at frequency of 30-40 kHz on the thermostatic ultrasonic bath. Seeds were sonicated at a constant temperature (25ºC) for 15 min. Ultrasound effect is reflected in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Our data show that pretreating seeds with ultrasound effectively promoted germination percentage and rate (Figure 1 , Table 2 ). This finding is consistent with previous studies in other species that have utilized ultrasound to promote seed germination (Babaei‐Ghaghelestany et al., 2020 ; Ding et al., 2018 ; Kratovalieva et al., 2012 ; Miano et al., 2015 ; Rifna et al., 2019 ). For example, Ding et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data show that pretreating seeds with ultrasound effectively promoted germination percentage and rate (Figure 1 , Table 2 ). This finding is consistent with previous studies in other species that have utilized ultrasound to promote seed germination (Babaei‐Ghaghelestany et al., 2020 ; Ding et al., 2018 ; Kratovalieva et al., 2012 ; Miano et al., 2015 ; Rifna et al., 2019 ). For example, Ding et al.…”
Section: Discussionsupporting
confidence: 92%
“…Our data show that pretreating seeds with ultrasound effectively promoted germination percentage and rate (Figure 1, Table 2). This finding is consistent with previous studies in other species that have utilized ultrasound to promote seed germination (Babaei-Ghaghelestany et al, 2020;Ding et al, 2018;Kratovalieva et al, 2012;Miano et al, 2015;Rifna et al, 2019). For example, Ding Ultrasound treatments are believed to induce changes in the seed coat, facilitating influx or efflux of water and mineral elements into cells (Miano et al, 2015;Qin et al, 2012) and/or to increase the activity of alpha-amylase enzyme and therefore the rate of starch metabolism (Yaldagard et al, 2007(Yaldagard et al, , 2008.…”
Section: Discussionsupporting
confidence: 91%
“…However, under similar Cu application treatment, ultrasonic seed treatment showed lower PN at flowering stage (Table 1). Ultrasonic seed treatment may cause physiobiochemical changes in seeds, e.g., elongation in coleoptiles and mesocotyl, thus accelerated seminal roots growth which may resulted in increased absorption of water and other mineral nutrients that ultimately led to enhanced growth and development of crop plants (Kratovalieva et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hassan et al [61] observed that 5 min LFUS treatment greatly improved the number of germinated sorghum grains from 78% (control) to 94%; a longer process decreased the germinated seeds, therefore they inferred that at high amplitude the treatment damaged cells and/or enzymes. Kratovalieva et al [62] studied LFUS application to different cereals and noticed significant effects on coleoptile and mesocotyl elongation. Oat and rye caryopses were very sensitive to LFUS stimulation (+119% and +65% growth, respectively), while triticale and wheat showed smaller increases.…”
Section: Low-frequency Ultrasound Application In Cereals and Pseudoce...mentioning
confidence: 99%